1997
DOI: 10.1007/s002689900311
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis and Open Groin Hernia Repair

Abstract: Antibiotic prophylaxis is not routinely given for nonimplant, clean operations, although this view has recently been challenged. We have conducted a randomized multicenter, double-blind prospective trial to compare co-amoxiclav with placebo in 619 patients undergoing open groin hernia repair. Altogether 563 (91%) patients fulfilled the protocol; 283 received co-amoxiclav and 280 placebo. There was no difference between the groups in the number of patients receiving local or general anesthetic, the type of repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1
15

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 7 publications
1
60
1
15
Order By: Relevance
“…In clean surgical interventions like breast cancer surgeries; antibiotic prophylaxis should be considered [13]. However; for other clean neck surgeries and hernia repair it is not recommended due to the low incidence of wound infection [15]. In Brazil Fonseca and Contemnor reported that 26% of patients were unnecessarily given antibiotics for surgical prophylaxis [16].…”
Section: Discussionmentioning
confidence: 99%
“…In clean surgical interventions like breast cancer surgeries; antibiotic prophylaxis should be considered [13]. However; for other clean neck surgeries and hernia repair it is not recommended due to the low incidence of wound infection [15]. In Brazil Fonseca and Contemnor reported that 26% of patients were unnecessarily given antibiotics for surgical prophylaxis [16].…”
Section: Discussionmentioning
confidence: 99%
“…In a randomised controlled trial of antibiotic prophylaxis, Taylor and co-workers 58 gave each discharged patient a diary card on which their GP or nurse was asked to record any suggestion of wound infection and details of any therapeutic intervention after discharge. Bacteriology culture swabs were also given to patients and they were asked to return them to the laboratory in the event of their wound discharging (wound infection defined as per the SISG definition: a purulent wound discharge or spreading erythema indicative of cellulitis, wound breakdown or dehiscence with clinical evidence of infection 29 ).…”
Section: Patient Diary Cardsmentioning
confidence: 99%
“…Antibiotic prophylaxis is not given, nor prophylaxis for thromboembolism in day-cases. 18,19 Intravenous access is established for the administration of sedation or other medication in all instances. A 100 mg Diclofenac suppository is given prior to the insertion of a field block of local anaesthetic (by the surgeon) or induction of general anaesthesia.…”
Section: Methodsmentioning
confidence: 99%